Developing an Islamic psychospiritual mental health model using Nominal Group Technique (NGT). - Mohd Zain, Rogayah; Mat Zin, Nazri; Junoh, Noraini; Mustapha, Ramlan; Yusoff, Yuslina; Sapiai, Nur Shaliza; Yusuf, Norazmila (Journal of Islamic, Social, Economics and Development, 2026)
The COVID-19 pandemic has caused a global mental health crisis, requiring culturally appropriate therapeutic interventions. Islamic psychospiritual approaches offer promising frameworks to address mental health challenges within Muslim communities. This study aims to evaluate the suitability of ten Islamic psychospiritual intervention components for supporting mental wellbeing through an expert consensus process using the Nominal Group Technique (NGT). A Nominal Group Technique was employed with [N=XX] experts in Islamic psychology, counseling, and mental health. Participants independently rated ten items/elements of psychospiritual intervention components on a suitability scale. The components includes dhikr (remembrance), muraqabah (mindfulness), tafakkur (contemplation), Quranic therapy, nafs management, and integrated Islamic counseling approaches. Analysis revealed that majority of the interventions achieved high suitability scores (86.67%-100%), indicating strong expert consensus on psychospiritual approaches. The highest-rated components were: Living Practice of Dhikr and Prayer, Tafakkur Training, Muraqabah as Islamic Mindfulness, Quranic Recitation Therapy, and Structured Prayer, with scores of [specific percentages]. These findings demonstrate expert preference for techniques integrating neurophysiological calmness with spiritual stability. Islamic psychospiritual interventions offer a holistic and culturally congruent framework for mental health promotion among Muslim populations. The high consensus scores validate these approaches of integration into mental health services and student wellbeing programs.